Strategi Manajemen Bisnis Syariah Dalam Situasi Pandemi Covid 19 Bidang Foodpreneur di Kabupaten Tangerang - Sakum; Khoirunisa, Junita (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
Every trial that Allah SWT gives always has wisdom that sometimes humans are unable to prevent, as currently being faced with getting a trial in the form of the Covid-19 virus. The Covid-19 virus is so that humans return to the teachings that have been exemplified by the Prophet Muhammad, especially in their business activities. This study aims to find out the strategies carried out by business actors in the Foodpreneur field in dealing with the Covid-19 Pandemic in Sharia business, the right strategy will lead business actors to survive during the Pandemic. The business sector must be able to adapt to today's world conditions, so there is a need for new strategies in business management. The method used in this research is qualitative with a Taman Snack study on business people in the Foodpreneur sector in Tangerang Regency. The results of the study show that the strategies used by business actors are to innovate products, improve service quality, read and capture digital opportunities, and adjust promotional materials. The strategy carried out by business actors is able to make business actors survive during the pandemic.